Cultivating Religious Values through Singing Activities in Group B of Alkhairaat Taipa Kindergarten, Palu - husni husni; Nurhayati (Universitas Tadulako, 2020)
The research objective was to determine the application of singing activities in the cultivation of religious values, to find out the cultivation of religious values ​​and to determine whether there was an effect of singing activities on the cultivation of religious values ​​in children in group B TK AL-Khairaat Taipa, Taipa Village, North Palu District . The formulation of the problem in this study is how the implementation of singing activities, how to cultivate religious values ​​and whether there is an effect of singing activities on the cultivation of religious values ​​in children in group B TK AL-Khairaat Taipa, Taipa Village, North Palu District. The research method used is a quantitative method with this type of research is experimentation. The research subjects were 14 children. Data were collected through observation and documentation sheets. Data collection techniques were carried out by using percentage techniques and t-test. The results of descriptive analysis research, the mean score of children, there were 30.95% in the BSB category, 49.99% in the BSH category, 16.67% in the MB category, and 2.39% in the BB category. Meanwhile, the results of the t-test showed that the t-value was -12,762 with a significant 0,000, because sig <0.05, it can be explained that H0 is rejected, H1 is accepted. Therefore, it can be concluded that singing has a significant effect on children's religious values.